Weight Change and Oedema Pattern in Different Types of Childhood Idiopathic Nephritic Syndrome - Islam, Md. Rafiqul; Matin, Abdul; Khan, Rita (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll ?Volume 2 Number 2 December 2010 ? Page 2-5 DOI: http://dx.doi.org/10.3329/jssmc.v2i2.12044